Ornamental Vegetables: Production Tips and Varieties to Produce or Sell - James L. Gibson (EDIS)
ENH-1044, a 5-page illustrated fact sheet by Dr. James L. Gibson, provides growers with information they need to take advantage of the increasing demand for cool season ornamental mustards and kale plants. Includes descriptions and cultural information for best performing varieties, references, and a table of recommended cultivars with seed source information. Published by the UF Department of Environmental Horticulture, August 2006.